Sistem Informasi Proses Produksi PT Tridaya Eramina Bahari - Iman Kumara, Salvian; Kusumawati, Arie (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
PT. Tridaya Eramina Bahari is a company engaged in the exporter of marine fish processing.This company does not yet have an integrated system. The process is still manual, making the length ofwork process and frequent errors. The length of the process makes it difficult for a corporate leader tomake a decision. This study aims to analyze and build information systems based on web productionprocess using laravel framework. System development method used is prototype. System modeling usesUML (unified Model Language). Database design using ERD (Entity Relationship Diagram). Testingsystem using black box method with alpha testing type. The result of this research is production processinformation system used by company side to facilitate employee job.